Persepsi Pengguna X Terhadap Cancel Culture Yang Dialami Abidzar Al Ghifari - Salsabila Ariani Romadhonie; Nazahah Salwa; Agista Riani Riswanmudi; Anastasya Amanda Putri (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
The cancel culture phenomenon is increasingly prevalent in the digital space, including on platform X. One prominent case is the cancel against Abidzar Al Ghifari due to his attitude which is considered arrogant and unprofessional. This research aims to understand X users' perceptions of Abidzar's cancel culture, using Cancel Culture theory (Eve Ng) and Social Judgment Theory (Muzafer Sherif) as analytical guidelines. This research uses a qualitative approach with an indepth interview method with two informants who are active X users. The results show that both informants support canceling as a form of social accountability. They view canceling not only as an emotional outburst, but also as a means of social control to uphold the responsibility of public figures. The practice of canceling is strengthened by a massive collective discourse, and is based on the motivation to maintain public morality and provide a deterrent effect. Nevertheless, informants also realize the negative potential of cancel culture if it is misused to attack personally or is carried out excessively. Therefore, cancel culture should be applied proportionally by considering ethics, context, and long-term impact. This research confirms that cancel culture has a function as a reflective social instrument, but requires critical understanding so that it does not shift into a form of symbolic violence in the digital space. Keywords: cancel culture, social media, social judgment